Intellectual extremism and its relationship to psychological defeat among university students (Journal of the College of Basic Education, 2025)
The current research aims to identify the relationship between intellectual extremism and psychological defeat among university students, as the research sample consisted of (200) male and female students at Shatrah University, with (85) males and (115) females, where the researcher used the scale (Amal Hussein, 2019) to measure intellectual extremism and the scale (Abu Halawa, 2013) to measure psychological defeat, and the research results showed the following:The research sample exhibits intellectual extremism.The research sample does not suffer from psychological defeat.There is an inverse, i.e., negative, and statistically significant relationship between intellectual extremism and psychological defeat.There is no difference between males and females in this relationship. The research then produced some recommendations and proposals.